2019
DOI: 10.3390/su11123447
|View full text |Cite
|
Sign up to set email alerts
|

How Societal Values Determine the Local Use of Forest Resources—Findings from the Rural Community Kegong (Northwest Yunnan, China)

Abstract: The transition from net deforestation to net reforestation in China has received much scientific attention, in the hope that, by understanding the underlying drivers and processes, it might be reproduced in other regions of the world. The scientific literature has suggested that this process was driven by the creation of off-farm opportunities and huge state afforestation programs by economic growth. Recent publications, however, have noted a lack of inclusion of local dynamics in this analysis. We used the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…A large body of research has already explored the relationships people have with treescapes and the values and benefits they provide, whether they are accessing and undertaking activities in woodlands or green spaces with trees (O'Brien & Morris, 2014; Saraev et al., 2021), or whether they are engaging with them through other means, such as visually, virtually or through livelihood activities (Marušáková & Sallmannshofer, 2019). Studies have also explored and identified these values with indigenous communities (Angarita‐Baéz et al., 2017; Plumb et al., 2012; Sangha et al., 2019), urban dwellers (Li et al., 2019), national park visitors (Považan et al., 2015; Sumner & Lockwood, 2020), rural communities (Lee et al., 2020; Nassl & Löffer, 2019), forest owners and managers (Aukema et al., 2011) and city park visitors (Arnberger et al., 2020; Rudl et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A large body of research has already explored the relationships people have with treescapes and the values and benefits they provide, whether they are accessing and undertaking activities in woodlands or green spaces with trees (O'Brien & Morris, 2014; Saraev et al., 2021), or whether they are engaging with them through other means, such as visually, virtually or through livelihood activities (Marušáková & Sallmannshofer, 2019). Studies have also explored and identified these values with indigenous communities (Angarita‐Baéz et al., 2017; Plumb et al., 2012; Sangha et al., 2019), urban dwellers (Li et al., 2019), national park visitors (Považan et al., 2015; Sumner & Lockwood, 2020), rural communities (Lee et al., 2020; Nassl & Löffer, 2019), forest owners and managers (Aukema et al., 2011) and city park visitors (Arnberger et al., 2020; Rudl et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, previous research into forest transition in China paid little attention to the micro-relationship between livelihood and land use and their further influence on forest transition. They mainly focused on the Returning Farmland to Forest Program (RFFP) [46,50], economic growth and government policies [3,18,[51][52][53], societal values about the forest resource [54] and natural disaster stimulation [55]. Moreover, questions regarding the time of forest transition in China and understanding of the process and mechanism of time and space variation of forest transition were not addressed adequately.…”
Section: Introductionmentioning
confidence: 99%